بيت المقدس في السياسة المملوكية - أحمد الخريسات, حنان (جامعة الوادي University of Eloued, 2016)
تهدف هذه الدراسة إلى تسليط الضوء على السياسة المملوكية تجاه بيت المقدس التي شهدت حالة من عدم الاستقرار عبر المراحل التاريخية وتعرضت للغزو الصليبي والمغولي ، غير أن قيام دولة المماليك وتصديها لأية تحالفات من شأنها إحداث التغيير في وضع المدينة ، كان له كبير الأثر في حمايتها من التحالفات المغولية مع الغرب الأوروبي ومن أية حملات صليبية بهدف استعادتها من جديد ، كما هدفت الدراسة إلى تسليط الضوء على السياسة الدينية تجاه بيت المقدس ، وما قدمه السلاطين المماليك من رعاية واهتمام اجتماعي وخيري إذ كانت محط رعايتهم واهتمامهم ولم يغفلوا عنها حتى في حالات عدم الاستقرار السياسي التي شهدتها الدولة في بعض الفترات . This study aims at throwing light on the Mamlkus’ political system towards (Bait Al – Maqdes ) which had witnessed inconstant and unstable conditions over the historical stages particularly the Mongols and Crusaders’ invasion. But the establishment of the Mamlkus’ state and its efforts against any interference in its affairs could have made a great change in defending it and keeping it away from the Mongols agreements with the European West to get it back. This study also aims at throwing light on the religious policy towards (Bait Al – Maqdes ) and on what the Mamluks’ Sultans provided from their social and charitable efforts as a kind of paying attention to it and because they had never forgotten it especially in its unstable political conditions that the state had experienced many years ago.
Keywords: بيت المقدس، السياسة المملوكية